WRITTEN AND ORAL FEEDBACK IN WRITING CLASS (RETAIN, 2020)
As one of the skills in English, writing plays an essential role for students, especially in the academic setting. In line with, sometimes students find writing skill challenging to learn, and it may not be easy for teachers to improve their writing ability. Consequently, teacher feedback is needed to enhance students' ability in writing. In order to consider the feedback quality implemented, we need to know from the learners' perspective. Therefore, this conceptual article aims to investigate the distinctive of both oral and written teacher's feedback in writing based on students' perceptions and see which teacher's feedback type is best in improving students' writing ability. The results show that, regardless of the feedback form, students' improvement in writing could have no relation between feedback choice and the quality of revisions. As such, it may be necessary to make practical and even workable discussions and concerns between students and teachers, that oral and written input can be combined to improve student writing better. By way of making the students and teacher feel realistic and even feasibly in the discussion, it is better to implement written feedback that followed by oral feedback. Keywords: Written feedback, Oral feedback, Writing Class